2015
DOI: 10.1007/s11837-015-1396-6
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of EAF Slag as Reinforcing Filler for Polypropylene Matrix Composites

Abstract: Electric-arc furnace (EAF) slag, the by-product of steel fabricated at the EAF, is in most cases still sent to dumps, with serious environmental consequences. This work shows an innovative, economically convenient application for EAF slag: its use as reinforcing filler for polypropylene. Composites based on polypropylene containing 10–40 wt.% of EAF slag particles were prepared by melt compounding followed by injection molding. A physical–chemical analysis of the EAF slag was performed to determine microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…The influence of stabilized FA as filler in epoxy resin matrix on the elongation at break is similar to that of calcium carbonate. As expected, increasing the filler amount in the epoxy matrix the elongation and the straight at break decrease, while the flexural modulus increases [45][46][47]. In general, the same content [% wt] of ash and calcium carbonate affects the composite flexural behavior similarly.…”
Section: Three Point Bending Testsupporting
confidence: 59%
“…The influence of stabilized FA as filler in epoxy resin matrix on the elongation at break is similar to that of calcium carbonate. As expected, increasing the filler amount in the epoxy matrix the elongation and the straight at break decrease, while the flexural modulus increases [45][46][47]. In general, the same content [% wt] of ash and calcium carbonate affects the composite flexural behavior similarly.…”
Section: Three Point Bending Testsupporting
confidence: 59%
“…Indeed, it was shown that aggregates containing EAF slags have excellent physical and chemical characteristics, and thus can be used in cement-treated materials [13]. EAF slags are also used in wastewater treatment [14][15][16], CO 2 sequestration [17], agriculture fertilizer or remedy for soil acidity [18], and reinforcing filler for composite materials [19,20]. The recycling of steel slag may be restricted because of the presence of potentially toxic elements-like Cr, V, Ba and Mo [21]-and leaching tests are mandatory to verify the release of toxic elements in the water [22].…”
mentioning
confidence: 99%
“…The slag employed in this research as filler has been produced by an electric arc furnace process, so that it is a "black" slag. In particular after slagging it has been treated by a specific system named Slag-Rec [17,31].…”
Section: Filler: Eaf Slagmentioning
confidence: 99%
“…EAF slag used as filler for PP matrix in [31] was produced by the same Slag-Rec system, but it derived from a different casting with respect to that used as filler for NBR, ELT, and epoxy matrixes.…”
Section: Filler: Eaf Slagmentioning
confidence: 99%
See 1 more Smart Citation